Bioactive Compounds of Seaweed Padina australis and Eucheuma cottonii as Sunscreen Raw Materials - Fevita Maharany; Nurjanah Nurjanah; Ruddy Suwandi; Effionora Anwar; Taufik Hidayat (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Seaweed is one of the main commodity which spread throughout Indonesian waters. Seaweed contains bioactive compounds which can serve as a defense form ultraviolet radiation. The purpose of this study was to obtain chemical composition, phytochemical compounds, vitamin E, and antioxidant activity of extract P. australis and E. cottonii. Chemical composition of P. australis moisture 87.25%; ash 2.34%; protein 1.05%, fat 0.58%; and carbohydrates 8.78% while E. cottonii moisture 76.15%; ash 5.62%; protein 2.32%; fat 0.11%; and carbohydrates 15.8%. The yield of P. australis extracts using methanol 4.55%; ethyl acetate 0.8%; and n-hexane 0.45%, yield of  E. cottonii extracts using methanol 6.6%; ethyl acetate 0.5%; and and n-hexane 0.35%. Vitamin E value of P. australis 162.75 μg/mL and E. cottonii 158.07 μg/mL. IC50 value of P. australis 87.082 ppm and E. cottonii  106.021 ppm. P. australis and E. cottonii contain phytochemical compound such as flavonoids, phenol hydroquinone, and triterpenoids, P. australis was also known contain tannins andsaponins.